IMPLIKASI PENGISIAN JABATAN HAKIM SEBAGAI PEJABAT NEGARA TERHADAP SISTEM PERADILAN - Anjasmana, Haris Kurnia (Faculty of Law, Tanjungpura University, 2021)
AbstractSince the implementation of judicial reform, the position of judges has changed to become State Officials. However, in practice, Judges are still civil servants, for example about the recruitment of Candidates for Judges in the Supreme Court for the 2017 Fiscal Year who still use the Civil Servant Candidate recruitment system (CPNS) that can be seen in the Supreme Court Regulation (PERMA) Number 2 of 2017 concerning Procurement of Judges. The identification of the problem in this paper is How the Problems of Filling Judges' Mechanism as State Officials Affect the Judicial System. The method used in this research is normative juridical. The specification is descriptive-analytical. This method uses secondary data material sourced from literature and related laws and regulations. Also, data analysis uses qualitative analysis. As for the research results, filling the position of a judge using the CPNS system is not a selection like other state officials; of course, it hurts the judicial system's independence because it currently is a state official. By using CPNS-style selection, judges will find it difficult to independently examine and decide a case, especially if it is related to cases that deal with the government; because of the dualism of a judge's position, judges must obey the government, which can interfere with the personal independence of judges and the independence of the Supreme Court as institutional.AbstrakSejak diterapkannya reformasi peradilan, kedudukan hakim telah berganti menjadi Pejabat Negara, Namun praktiknya, Hakim masih berkedudukan sebagai Pegawai Negeri, contohnya berkaitan dengan rekrutmen Calon Hakim di Lingkungan Mahkamah Agung Tahun Anggaran 2017 yang masih menggunakan sistem rekrutmen Calon Pegawai Negeri Sipil (CPNS) yang dapat dilihat pada Peraturan Mahkamah Agung (PERMA)Â Nomor 2 Tahun 2017 tentang Pengadaan Hakim. Adapun identifikasi masalah dalam makalahÂ ini adalah Bagaimana Problematika Mekanisme Pengisian Jabatan Hakim Sebagai Pejabat Negara Berpengaruh Terhadap Sistem Peradilan. Metode yang digunakan penelitian ini adalah yuridis normatif. Spesifikasi bersifat deskriptif analitis. Metode ini menggunakan bahan data sekunder yang bersumber dari bahan kepustakaan dan peraturan perundang-undangan yang terkait. Selain itu analisis data menggunakan cara analisis kualitatif. Adapun hasil penelitian yaitu Proses pengisian jabatan hakim meggunakan sistem CPNS bukan seleksi layaknya pejabat negara lain tentu mencederai independensi sistem peradilan karena saat ini merupakan pejabat negara. Dengan menggunakan seleksi ala CPNS, hakim akan sulit untuk independen memeriksa dan memutus suatu perkara, apalagi jika terkait perkara yang berurusan dengan pemerintah, karena dualisme kedudukan hakim ini, hakim harus taat kepada pemerintah, itulah yang dapat mengganggu independensi personal hakim maupun independensi Mahkamah Agung secara kelembagaan.